Case Report: Endovascular therapy for an iatrogenic vertebrojugular arteriovenous fistula and pseudoaneurysm induced by multiple vascular procedures - Huai-Xue Mi; Chun-Mei Guo; Shan-Liang Chen; Jun Zhang; Zhi Gao; Li Hongxin; Ju Han (Frontiers in Cardiovascular Medicine)
Vertebrojugular arteriovenous fistula (VJAVF) and vertebral artery pseudoaneurysm (VAPA) are usually caused by iatrogenic and penetrating traumas. The concurrence of these two entities originating from different ostia of the vertebral artery (VA) is extremely rare. The history of repeated open-heart surgery and the application of central venous catheterization during anesthesia increased the risk of VA injuries and its complications of the VJAVF and VAPA. The patient, who complained of dizziness, was initially diagnosed with bradycardia and aortic paravalvular leak. However, the symptoms persisted even after permanent pacemaker implantation and transcatheter closure of the aortic paravalvular leak. Ultrasonography, CT angiography, and intraoperative right subclavian arteriography showed a VJAVF originating from the right VA and draining into the right internal jugular vein. A VAPA originated from another ostium of the right VA without a drainage vessel. Using the endovascular technique, a 4 mm stent graft was deployed in a 3.6 mm VA to cover both the VJAVF and the VAPA ostia. The symptoms of dizziness disappeared. The VJAVF and VAPA were completely sealed without recurrence at the 6-month follow-up.